Understanding the needs of nutrition intake on athletes - Sasmarianto; Raffly Henjilito; Zulrafli; Kamarudin; Novia Nazirun (UIR Press, 2021)
Physical fitness is influenced by the food they consume. Nutritious food can increase the athlete's stamina so that athlete's achievement will be easily achieved. Fulfilling the need for nutritional intake requires a good level of understanding of the importance of the nutritional intake needs of athletes, especially soccer athletes at SMA Negeri Sport Riau Province. The purpose of the study is to measure the level of understanding of the nutritional intake needs of adolescent soccer athletes at SMA Negeri Sport Riau Province. This type of research is evaluation. The method used in this study is a survey method with data collection techniques using a questionnaire. The data collection technique is carried out using a questionnaire or questionnaire method by testing the level of validity and reliability. The population in the study amounted to 35 male soccer athletes at the Riau Province Sports State Senior High School. The sampling technique uses total sampling. Data analysis uses quantitative descriptive as outlined in the form of a percentage. The results shows that the level of understanding of the nutritional intake needs of soccer athletes at the Riau Province Sports High School can be seen that 65.7% gives a good assessment. This indicates that the level of understanding of the nutritional needs of athletes is in the good category so this needs to be maintained. Likewise, the athletes' understanding of the athlete's daily nutritional adequacy and the regulation of the athlete's nutritional intake during the training period is in the good category. So it can be concluded that the level of understanding of the nutritional intake needs of soccer athletes is in the good category.